D Development of Articulate Storyline of Human Respiratory System Materials in V-Class Students at Pati - Zahratunnisa, Mutiara Devy; Aditia Ismaya, Erik; Hilyana, F. Shoufika (Bulletin of Science Education, 2024)
The learning media in school affects less learning. That's why specialists promote stories that are interpreted by the media. In this review, the experts developed techniques that use innovative work (research and development) using the ADDIE model. Date collection techniques include observations, interviews, documentation, and lifting. Data analysis used is qualitative and quantitative data analysis (uji validasi dan uji angket respon siswa). Learning with software articulate storyline that got an average of 95.5% of the material expert validation test results and 95.2% of the media expert evaluation results with a very valid category. The analysis of the elevation needs of students obtained a presentation of 34.10% that students are still having difficulties in the subject of IPAS. The results of the validation of materials 1 and 2 in terms of material compatibility, language suitability, usability, and suitability with the pupils are very valid, so they can be used to structure the story line. We obtained a maximum r value of 0.998 > 0.349 and a rehabilitation test with a cronbac alpha value of 0,687 > 0.6, so the validity test results indicate that the data is valid. So that the Media Articulate Storyline can be used by teachers for innovative media. Keywords: Articulate Storyline, Human Respiratory System, Learning Media